2019
DOI: 10.1186/s43031-019-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

The future challenge of Earth science education research

Abstract: This article addresses the question of what the future directions and emphases of the research in the earth science education field ought to be. During the past 30 years, Earth science education research has established a solid theoretical foundation, as well as practical strategies and techniques, for a meaningful teaching of earth science from K-12. However, the quality of this research, and the growing need for knowledge in Earth science, have done little to improve the low profile of ESE in schools worldwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 28 publications
0
52
0
3
Order By: Relevance
“…The study of the interacting Earth systems-within the dimension of deep time and the large spatial scale of geological processes-will enable students to appreciate the realistic influence of humans on the Earth in deep time perception. This approach moves students away from the traditional altruistic approach to environmental awareness towards a more egocentric and geocentric perception [40,41].…”
Section: Earth System Environmental Insight and Earth Science Sustamentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the interacting Earth systems-within the dimension of deep time and the large spatial scale of geological processes-will enable students to appreciate the realistic influence of humans on the Earth in deep time perception. This approach moves students away from the traditional altruistic approach to environmental awareness towards a more egocentric and geocentric perception [40,41].…”
Section: Earth System Environmental Insight and Earth Science Sustamentioning
confidence: 99%
“…Levy and collaborators have shown that environmental behaviour is often driven by "egoistic" concerns rather than by altruistic views and motivations [41]. They claimed that their findings suggest that part of the failure of all these campaigns to establish a significant and sustainable change in the public's environmental behaviour (at least in several countries) may be related to their altruistic approach.…”
Section: Earth System Environmental Insight and Earth Science Sustamentioning
confidence: 99%
“…However, these issues are complex and reflect and result from the Earth's own complexity as a system; to solve them, specific competencies and approaches are required. Thus, educating society about the Earth system is crucial for the daily life and future of humanity given the relationship between the human species and the planet [1,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The Earth system is composed of five deeply interdependent and related subsystemsatmosphere, biosphere, cryosphere, geosphere, and hydrosphere-with constant trades of matter and energy [18,19]. This systemic notion of the Earth system's behavior is relatively recent, therefore its perception by the majority of citizens may not be a reality as it is not yet an applied approach in schools in many countries [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation